Impaired Fracture Healing in Sarco‐Osteoporotic Mice Can Be Rescued by Vibration Treatment Through Myostatin Suppression. Issue 2 (3rd October 2019) - Zhang, Ning; Chim, Yu Ning; Wang, Jinyu; Wong, Ronald Man Yeung; Chow, Simon K. H.; Cheung, Wing‐Hoi
ABSTRACT: Sarcopenia is highly prevalent in fragility fracture patients and is associated with delayed healing. In this study, we investigated the effect of low‐magnitude high‐frequency vibration (LMHFV) on osteoporotic fracture with sarcopenia and the potential role of myostatin. Osteoporotic fractures created in sarcopenic SAMP8, non‐sarcopenic SAMR1 were randomized to control or LMHFV (SAMP8, SAMR1, SAMP8‐V, or SAMR1‐V) groups. Healing and myostatin expression were evaluated at 2, 4, and 6 weeks post‐fracture. In vitro, conditioned‐media were collected from myofibers isolated from aged and young SAMP8 or C2C12 myoblasts with or without LMHFV. Osteoblastic MC3T3‐E1 under osteogenic differentiation were treated with plain or conditioned‐medium (±myostatin propeptide). LMHFV significantly enhanced callus formation was in non‐sarcopenic SAMR1 mice; but the enhancement effect was not significant in SAMP8 mice at week 2. Myostatin expressions in callus and biceps femoris of SAMP8 group were significantly higher all groups with significant negative correlation with callus size ( R 2 = 0.7256; p = 0.0004). Mechanical properties (week 4) and callus remodeling (week 6) were inferior in SAMP8 versus SAMR1 and were significantly enhanced by LMHFV. Alkaline Phosphatase (ALP) and Runx2 expression of MC3T3‐E1 was lower in aged myofiber compared with young, but upregulated by LMHFV or myostatin inhibition; also confirmed with C2C12. LMHFV enhanced early callus formation, microarchitecture, callus remodeling and mechanical properties of fracture healing in both SAMP8 and SAMR1; however, more effective in non‐sarcopenic SAMR1 mice. Impaired fracture healing in sarcopenic SAMP8 mice is attributed by elevated myostatin expression in callus and muscle, which correlated negatively with callus formation. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:277‐287, 2020